A new gestational diabetes mellitus model: hyperglycemia-induced eye malformation via inhibition of Pax6 in the chick embryo - Shi-Jie Zhang; Yi-Fang Li; Rui-Rong Tan; Bun Tsoi; Wen-Shan Huang; Yi-Hua Huang; Xiao-Long Tang; Dan Hu; Nan Yao; Xuesong Yang; Hiroshi Kurihara; Qi Wang; et al. (The Company of Biologists, 2016)
Gestational diabetes mellitus (GDM) is one of the leading causes of fetal malformations. However, few models have been developed to study the underlying mechanisms of GDM-induced fetal eye malformation. In this study, a high concentration of glucose (0.2 mmol per egg) was injected into the air sac of chick embryos on embryo development day (EDD) 1 to develop a hyperglycemia model. Results showed that 47.3% of embryonic eye malformation happened on EDD 5. In this model, the key genes regulating eye development, Pax6, Six3 and Otx2, were downregulated by hyperglycemia. Among these genes, the expression of Pax6 was the most vulnerable to hyperglycemia, being suppressed by 70%. A reduction in Pax6 gene expression induced eye malformation in chick embryos. However, increased expression of Pax6 in chick embryos could rescue hyperglycemia-induced eye malformation. Hyperglycemia stimulated O-linked N-acetylglucosaminylation, which caused oxidative stress in chick embryos. Pax6 was found to be vulnerable to free radicals, but the antioxidant edaravone could restore Pax6 expression and reverse eye malformation. These results illustrated a successful establishment of a new chick embryo model to study the molecular mechanism of hyperglycemia-induced eye malformation. The suppression of the Pax6 gene is probably mediated by oxidative stress and could be a crucial target for the therapy of GDM-induced embryonic eye malformation.